RESOURCE-SAVING PRODUCTION OF SUGAR CONFECTIONERY ENRICHED WITH FUNCTIONAL PLANT INGREDIENTS - Pushmina I.N.; Pervishina G.G.; Zakharova L.M.; Pushmina V.V. (Техника и технология пищевых производств)
In recent years, Russia has shown the increased interest of consumers to food products enriched with natural bioactive ingredients. The fundamental resource-saving technological scheme of production of fortified sugar confectionery has been developed. The authors justified the choice of raw materials of plant origin: fresh cowberry ( Vaccinium vitisidea ) and cranberry ( Vaccinium oxycoccos L. ) fruits, air-dried oregano shoots ( Origanum vulgare L. ) growing in the Krasnoyarsk region as functional ingredients. The usefulness of the development of functional purpose sugar confectionery from cowberry and cranberry fruits soaked in "Oregano" syrup based on an aqueous extract of oregano shoots has been proven. The change in vitamin C concentration in plant raw materials under the influence of heat treatment has been studied, which helped to justify the optimum thermal conditions for ensuring the preservation of vitamin C. A distinctive feature of the developed resource-saving technological scheme is pre-saturation of fruit and berry raw material with the origanum complex of biologically active substances and integrated use of original plant ingredients. The research of microbiological, toxicological, physical and chemical indices of the enriched sugar confectionary - «Cranberry in chocolate», «Cowberry in chocolate», proved the sanitary and hygienic safety and functional qualities of the products.